Schedule Actual Proyek dengan Metode Precedence Diagram Method (PDM) dan Program Evaluation and Review Technique (PERT ) pada Proyek Pembangunan Pasar - Muhammad Kholish Muwaffa; Gunaedy Utomo; Reno Pratiwi (Jurnal Talenta Sipil, 2026)
The construction and development of the Klandasan Block C Market Distribution Facility in Balikpapan City is a strategic construction project that plays an important role in supporting the economic activities of the local community. This project requires optimal planning and time management to ensure that all stages of the work can be completed according to the target. Problems that often arise in the implementation of construction projects are delays due to uncertainty in the duration of activities and a lack of synchronization between interdependent activities. Therefore, this study was conducted with the aim of identifying critical paths and calculating the probability of successful project completion using the Precedence Diagram Method (PDM) and Program Evaluation and Review Technique (PERT) approaches. The PDM method is used to describe the dependency relationships between activities, determine the critical path, and identify activities that have the potential to cause delays. Meanwhile, the PERT method is applied to estimate the project completion time by considering the variability of activity duration through three time estimates, namely optimistic, realistic, and pessimistic. The analysis results show that the project has several activities that are classified as critical and require intensive monitoring of resource allocation to prevent schedule deviations. Based on the calculations, projects with a planned duration of 150 days have a high probability of being completed on time. In conclusion, the combination of PDM and PERT methods provides effective results in the process of planning and controlling project schedules, helping project managers determine activity priorities, optimize time efficiency, and minimize the risk of construction delays.